Pelatihan Manajemen Puskesmas Dengan Metode 3P di Puskesmas Sempaja Kota Samarinda - Adrianto, Ratno; Rahayu, Eka Putri; Sumarni, Sumarni; AR, Chaerunnisa; Isnaniah, Enny (Penerbit Goodwood, 2025)
Purpose: The aim of this activity was to make primary health care capable of doing management and optimum healthcare activity. Methodology/approach: This activity was held in October 2024, placed in Puskesmas Sempaja. These activities were mostly two days of training in 3P Primary Health Care Management. Results/findings: There was an increase in knowledge in the good category from 69,6% to 87%. This result shows that there was an increase in participant knowledge before and after participating in the 3P primary health care management training. The enthusiasm of the participants was also very high in this training. Conclusions : A community service activity titled “Health Center Management Training Using the 3P Method at Puskesmas Sempaja in the Humid Tropical Forest Area of Samarinda City” was conducted over two days. The program involved 23 participants, all of whom were employees of Puskesmas Sempaja. The results indicated a significant improvement in knowledge, with the percentage of participants categorized as having